2014
DOI: 10.1016/j.avb.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated community response components for victims of intimate partner violence: A review of the literature

Abstract: Intimate partner violence (IPV) against women is a serious problem throughout the world. Each year a substantial number of women experience psychological, physical, and sexual aggression from an intimate partner, with many women experiencing serious mental and physical health outcomes as a result of their victimization. A number of services are available to women who sustain IPV (e.g., shelters, advocacy, legal protection), and the combination of these services has been termed a Coordinated Community Response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 72 publications
2
70
0
Order By: Relevance
“…A lack of local services, or a lack of trauma-informed and prepared local providers, can pose an ethical quandry for healthcare professionals because it could endanger or harm a victim to be identified but then receive inadequate follow-up help. One possibility is that providers adapt the "coordinated community response" model that domestic violence providers have used throughout the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 U.S. (Shepard, Falk, & Elliott, 2002;Shorey, Tirone, & Stuart, 2014). More information about the coordinated community response can be found here:…”
Section: Discussionmentioning
confidence: 99%
“…A lack of local services, or a lack of trauma-informed and prepared local providers, can pose an ethical quandry for healthcare professionals because it could endanger or harm a victim to be identified but then receive inadequate follow-up help. One possibility is that providers adapt the "coordinated community response" model that domestic violence providers have used throughout the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 U.S. (Shepard, Falk, & Elliott, 2002;Shorey, Tirone, & Stuart, 2014). More information about the coordinated community response can be found here:…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that intimate partner violence is positively associated with factors such as age (Millett, Seay, & Kohl, 2015;Walker, Bowen, & Brown, 2013), residency (Tang & Lai, 2008), marital duration (Babu & Kar, 2010), education (Shorey, Tirone, & Stuart, 2014;VanderEnde, Yount, Dynes, & Sibley, 2012), occupation (Heath, 2012;Krishnan et al, 2010), economic status (Hines, 2007;Koenig, Stephenson, Ahmed, Jejeebhoy, & Campbell, 2006), problem alcohol use (Chang, Shen, & Takeuchi, 2009;Jewkes, Levin, & Penn-Kekana, 2002), traditional ideas (Lichter & McCloskey, 2004;Taylor, Nair, & Braham, 2013), gender inequity (Gomez, Speizer, & Moracco, 2011), liberal ideas on woman's role (Jewkes et al, 2002), culture (Wendt, 2009), witnessing parental violence in childhood (Abrahams, Jewkes, Laubsher, & Hoffman, 2006;Speizer, 2010) and attitude toward IPV (Fincham, Cui, Braithwaite, & Pasley, 2008;Stith, Smith, Penn, Ward, & Tritt, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Researchers’ and practitioners’ “growing awareness” of the complexity of DV has evolved into the understanding that “keeping women safe requires the coordinated effort of multiple systems” (Cattaneo and Goodman, : 156). Innovative responses to addressing DV have increasingly relied on what are known as community‐coordinated responses (CCRs), which attempt to empower the victim by coordinating multiple responses for their cases, with the ultimate goals of providing better case outcomes, victim participation, and victim safety (Cattaneo et al., : 1244; see also, Shorey, Tirone, and Stuart, ; Sullivan, ). This approach assumes that CCRs cannot be as effective if they are restricted to criminal legal system responses and do not “include a more victim‐informed mission that engages social justice agencies, clinics, housing and other organizations to meet victims’ needs” (Koss et al., : 1026; see also Cerulli et al., ; Shorey et al., ).…”
Section: Nonpolice‐related Research Findings On Domestic Violence In mentioning
confidence: 99%